Genetics of silicon content in upland rice under drought condition - Suraporniboon P. (2014)
Genetics of silicon (Si) content in upland rice was studied under drought condition at tillering stage during the 2006 growing season by using the six basic generations (P1, P2, F1, F2, Bc1.1, and Bct.2). The objective was to estimate the inheritance of Si content in upland rice. The result indicates that Si content in upland rice genotypes is controlled by a group of quantitative genes each with small effect. The genetic variance component analysis revealed that additive genetic variance (VA) played an important role in controlling Si content in upland rice tissues. The heritability study of Si content showed that narrow-sense heritabilities (h2n) in 45-day old leaf blades and in the leaf blade, stem, root, and hull at harvesting stage were 0.55, 0.60, 0.68, 0.56, and 0.66, respectively. These results suggested that Si content in upland rice tissues can be employed as selection criteria in breeding for drought tolerance in upland rice if crossing is made between parents with high Si contents followed by efficient selection.